ViiV HEALTHCARE ASSISTANCE TO THE SADAR HATI FOUNDATION IN THE HARM REDUCTION PROGRAM - Maria Veri Diana B.Y; Bagus Subekti Nurwantoro; Tanti Nurgiyanti; Yeyen Subandi (Indonesian Journal of Social Sciences, Policy and Politics, 2023)
This study aims to find out how the implementation of assistance from ViiV Healthcare to the Sadar Hati Foundation Malang in implementing the Harm Reduction program. This research uses a descriptive qualitative method, and interviews with related parties. International relations continue to experience developments along with changing times, especially as a result of globalization, which has had significant impacts or changes in international relations that have crossed national jurisdictional boundaries, because various dynamics always appear in every implementation. One of the crucial dynamics is the emergence of various problems both at the regional and global levels. One of the problems that is currently a global focus is the abuse of narcotics that are not for medical needs. Narcotics can be said to be dangerous when the use of narcotics has exceeded the consumption limit so this can also cause various impacts that become a threat to human life so it requires efforts to achieve human security. In this writing, the author analyzes using the concept of human security. With the implementation of the assistance provided by ViiV Healthcare to the Sadar Hati Foundation, which is a grant to run the program, one of which is harm reduction, in which the Foundation provides education, outreach, assistance to treatment by providing facilities to support the sustainability of the program.